The Current State of Diversity in Orthopaedics - Payares, Monica (Journal of the Pediatric Orthopaedic Society of North America, 2023)
The 2022 POSNA Annual Meeting Pre-course, the last of its kind, was dedicated to “Improving Patient care through Diversity, Equity and Inclusion,” showing the continued commitment of the organization to these vital topics in the continued growth of our field. Orthopaedic surgery remains the least diverse subspecialty. Although studies show representation of women and underrepresented minorites (URM) is increasing in orthopaedics, it is increasing at a slower rate than other surgical subspecialties. These issues were thought to stem from a lack of pipeline programs. Recent data, however, reveal that rates of attrition during residency (defined as either withdrawal or dismissal) are disproportionately higher for underrepresented groups. In addition, rates at which URM and women hold leadership positions in organizational and society boards are lower. Lack of diversity in orthopaedics cannot be explained solely by a lack of matching residents. Mentorship, sponsorship, and allyship are necessary for URMs and women to succeed throughout training and their careers.